Factors Affecting the Incidence of Scabies Among Female Students at Nurul Huda Boarding School - Rana Anas Nabila; Selviana Selviana; Linda Suwarni (Griya Eka Sejahtera, 2026)
Background: Scabies is a persistent public health problem in densely populated educational institurions such as Islamic Boarding Schools. Motivated by the high vulnerability in Mempawah Regency, this study aimed to identify personal hygiene and environmental sanitation factors associated with scabies incidence among female students at the Nurul Huda Islamic Boarding School to support effective prevention strategies.Methods: A quantitative observational study employing a cross-sectional design was conducted in October 2025, involving 69 female students selected through total sampling. Primary data were collected using structured questionnaires on personal hygiene, as well as direct physical observation checklists to assess dormitory environmental parameters. Data were analyzed using univariate and bivariate Chi-Square test (p = 0.05).Results: Scabies prevalence among respondents was high, reaching 76.8%. Physical environmental parameters (occupancy density, humidity, and lighting) collectively failed to meet national health standards (100%). Bivariate analysis revealed that towel hygiene (p = 0.008) and clothing hygiene (p = 0.002) were statistically significant risk factors. Conversely, Knowledge level (p = 0.364), bathing habits (p = 0.675), and bedding habits (p = 0.096) showed no significant associatin, driven by a floor effect resulting from the overall unhealthfull communal environment.Conclusion: High scabies prevalence is directly asscociated with unhygienic towel and clothing management, exacerbated by substandard dormitory physical sanitation environmental improvements (enhacing ventilation and natural lighting) with strict enforcement of personal hygiene compliance, such as ironing clothes at high temperatures and prohibiting item sharing.